قياس الاشعاعات البيئية في قسم الفيزياء في جامعة تشرين - جبور, جبور; ملحم, جهاد; كتاني, دانيال; جبيلي, هيثم; موسى, محمد (Latakia University Journal -Basic Sciences Series, 2018)
We present here some results obtained from the measurements of the environmental radiation at the Physics Department of Tishreen University, in the energy range 50KeV - 2.8MeV, by using a compact scintillation NaI(Tl) detector, low-time recovery and reliable. The detected radiation is essentially due to cosmic radiation and to the airborne radioactivity, but no radiation from other sources have been found. نقدم هنا بعض نتائج قياس الاشعاعات البيئية المأخوذة في قسم الفيزياء بجامعة تشرين، ضمن المجال الطاقي الواقع بين 50 كيلو الكترون فولط (50 keV) و2.8 ميغا الكترون فولط (2.8 MeV)، وذلك باستخدام كاشف ومضي NAI(Tl) مدمج (موثوق) وزمن الاستعاده له قصير. إن الاشعاعات المكتشفة ناتجة بشكل أساسي عن الاشعاعات الكونية والنشاط الاشعاعي البيئي المحيط بمكان القياسات، والاشعاعات المنقولة جواً، ولم يُلاحظ أي اشعاعات ناتجة عن منابع أخرى.